Arcana coelestia = Heavenly arcana which are in the sacred scripture or word of the Lord laid open, together with wonderful things which were seen in the world of spirits and in the heaven of angels - Swedenborg, Emanuel (New Church Printing Society, 1837)
v. 1-3. Genesis.